2022
DOI: 10.1111/ina.13172
|View full text |Cite
|
Sign up to set email alerts
|

Association of indoor noise level with depression in hotel workers: A multicenter study from 111 China's cities

Abstract: The noise level is associated with stress, 1 annoyance, 2 sleep disturbance, 3 cardiovascular disease, 4 and impaired cognitive performance, 5 particularly loud noise such as airports and their surroundings, 6,7 traffic road noise, 8,9 urban public activity space, 10 and recreational settings. 11,12 Meanwhile, the general population is exposed to multiple chronic or low-frequency noise sources, such as air conditioner noise and ventilation noise, due to occupational and residential exposure. Long-term exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
2
1
0
Order By: Relevance
“…In their findings, people exposed to significant traffic noise had a 1.29 times higher relative risk of depressive symptoms than those exposed to lower levels of noise 34 . In addition, our results align with those of previous study, which confirmed the association between workplace noise exposure and mild depressive symptoms in workers using the PHQ-9 index 35 . Drawing from both prior research and our own findings, it has come to light that exposure to noise has adverse psychological impacts.…”
Section: Discussionsupporting
confidence: 92%
“…In their findings, people exposed to significant traffic noise had a 1.29 times higher relative risk of depressive symptoms than those exposed to lower levels of noise 34 . In addition, our results align with those of previous study, which confirmed the association between workplace noise exposure and mild depressive symptoms in workers using the PHQ-9 index 35 . Drawing from both prior research and our own findings, it has come to light that exposure to noise has adverse psychological impacts.…”
Section: Discussionsupporting
confidence: 92%
“…A previous investigation examining the impact of regional tra c noise on depressive symptoms revealed that people exposed to signi cant tra c noise had a 1.29 times higher relative risk of depressive symptoms than those exposed to lower levels of noise 22 . In addition, our results support the ndings of a previous study that con rmed the association between workplace noise exposure and mild depressive symptoms in workers using the PHQ-9 index 23 .…”
Section: Discussionsupporting
confidence: 91%
“…In addition, our results also add to the evidence that a lack of light and humidity are associated with depressive symptoms. This conclusion has been confirmed by some reports [45,46]. Overall, the traditional adverse working environment factors, such as noise, lack of sunlight, and humidity, are still widespread and damaging to human health.…”
Section: Current Status Of Depressive Symptoms and The Observed Facto...supporting
confidence: 53%